Penerapan Elemen Budaya Lokal Nusantara terhadap Desain Arsitektur Hotel dan Resort Amanjiwo di Kabupaten Magelang - Fasya, Putri Madina; Arfianti, Ami (Universitas Medan Area, 2025)
The application of local Indonesian culture in architectural design has become the main focus. This study aims to explore how local Indonesian culture is integrated into the architectural design of the Amanjiwo Hotel and Resort, located in Magelang Regency, Indonesia. The architectural design shows that Amanjiwo combines elements of local Indonesian culture, including art, traditional architecture and local philosophy, in its design. The concept of using local materials, the layout based on local traditions, and the integration of traditional art and ornaments all contribute to an atmosphere that enriches the guest experience. This research can provide a better understanding of the importance of accommodating local culture in the development of hospitality properties, not only as a decorative element, but also as a foundation for creating local identity and memorable experiences for guests. The results of this research are to strengthen awareness of cultural sustainability and the importance of paying attention to the local context in the development of the Amanjiwo Hotel and Resort. Future research could broaden this scope by comparing the application of local culture in architectural design. Maintaining the values found in the physical structure and outdoor space of the Amanjiwo Resort related to Javanese cultural and traditional architecture is the main focus.